In search for new meteorite dense collection area in the Sor Rondane mountains - Debaille, Vinciane; Schönbächler, Maria; Valdes, Maria; Maeda, Ryoga; Poudelet, Manu; Goderis, Steven; Heck, Philipp; Tollenaar, Veronica; Zekollari, Harry; Claeys, Philippe (2023)
The 14th Symposium on Polar Science/Ordinary sessions [OA] Antarctic Meteorite, Tue. 14 Nov. / 3F Multipurpose Conference room, Institute of Statistical Mathematics conference object